Across the wide prairie: Exploring fear of crime in a small Canadian municipality. Issue 2 (June 2021) - Hodgkinson, Tarah; Lunney, Kate
Although fear of crime is well-researched in urban domains, the predictors of fear of crime in non-urban contexts are less established. Using a sample of 559 people, this study aims to address this gap by evaluating the role of individual and ecological-level predictors on fear of crime in a small Canadian municipality. Key findings of this study include support for the influence of social cohesion, informal social control and social and physical disorder on fear in a small municipality. However, no clear relationship is found between gender and fear of crime. Additionally, nuanced relationships between social predictors and fear emerge that may be uniquely explained by non-metropolitan context. The findings have implications for the use of urban-based criminological theories of fear and for the use of crime prevention and fear reduction strategies in non-metropolitan contexts.